2019
DOI: 10.1186/s40463-019-0336-9
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of two tertiary care dizziness clinics: A multidisciplinary chronic dizziness clinic and an acute dizziness clinic

Abstract: BackgroundVertigo remains a diagnostic challenge for primary care, emergency, and specialist physicians. Multidisciplinary clinics are increasingly being employed to diagnose and manage patients with dizziness. We describe, for the first time in Canada, the clinical characteristics of patients presenting with chronic and acute dizziness to both a multidisciplinary chronic dizziness clinic (MDC) and a rapid access dizziness (RAD) clinic at The Ottawa Hospital (TOH).MethodsWe performed a retrospective review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 29 publications
3
36
1
1
Order By: Relevance
“…Staibano et al observed a significant proportion of females for dizziness [ 19 ]. Women are believed to be more sensitive to dizziness and imbalance and feel a greater influence on their daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…Staibano et al observed a significant proportion of females for dizziness [ 19 ]. Women are believed to be more sensitive to dizziness and imbalance and feel a greater influence on their daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…Functional comorbidity is very common in patients with chronic dizziness (Staibano et al., 2019). Approximately 30%–50% of persistent dizziness cannot be fully explained by an identifiable medical illness (Schmid et al., 2011), and these patients mostly do not reveal any pathological results in technical diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 More recent studies from centers that included PPPD in their diagnostic schema found that number was reduced to fewer than 2% of new patient evaluations. 11,12 Moreover, long-standing symptoms nonspecifically attributed to chronic vestibulopathy in the past were more properly diagnosed as PPPD.…”
mentioning
confidence: 99%
“…13,14 In tertiary centers, these conditions constituted the principal diagnosis in 15 to 20% of all patients presenting for evaluation of vestibular symptoms, making them the most common diagnoses among young to middle-aged adults and the second most common among all adults, trailing only benign paroxysmal positional vertigo. Based on these older data and the most recent reports from tertiary neuro-otologic practices, 11,12 PPPD would be expected to rank among the top-three diagnoses encountered in referral centers, along with benign paroxysmal positional vertigo and vestibular migraine. The incidence and prevalence of PPPD in primary care and the general population are not known.…”
mentioning
confidence: 99%